Demulsification of Crude Oil Emulsions via Microwave Assisted Chemicals (Environmental Friendly) - Nur Hafizah, Hussin (2013)
Demulsification is a process of emulsion breaking. It is important in industry application such as waste water treatment, refinery and painting industry. Microwave and chemical heating is the most widely used method of water in oil demulsification. In this research, the combination of microwave and chemical is used to increase the efficiency of water in oil demulsification. To prevent the environmental issues, natural chemical is used in this research which is Diethanolamide of coconut fatty acid. The effectiveness of microwave assisted natural chemical in demulsification was assessed experimentally with two different power of microwave which are 450 and 600, and two different concentration of Diethanolamide of coconut fatty acid which are 0.5% and 1.5%. The water in oil emulsion was prepared by using artificial emulsifier. Artificial emulsifiers used are Triton X-100, Low Sulphur Wax Residue (LSWR) and Span 83. The natural chemical (Diethanolamide of coconut fatty acid) were added in the emulsion to increase the performance before heating the emulsion with microwave. The result shows that demulsification by using microwave assisted natural chemical was faster and more environmental friendly compared to conventional method.